Revisiting the quiet life hypothesis in banking using nonparametric techniques - Färe, Rolf; Grosskopf, Shawna; Maudos, Joaquín; Tortosa-Ausina, Emili (Journal of Business Economics and Management, 2014)
Early studies testing the quiet life hypothesis in banking found strong evidence that banks in more concentrated markets exhibit lower cost efficiency levels. More recent studies have reexamined the issue in different contexts with mixed results. These approaches are based on stipulating a linear relationship between market power and efficiency in banking, which might be problematic, as suggested by the literature on efficiency analysis. We explore how bank cost efficiency measures are related to market power using flexible techniques, which are more consistent with those employed to measure efficiency in the first stage of the analysis. Our study focuses on the Spanish banking industry, which has been experiencing substantial change in the last few years, combining institutions with different ownership structures and business models. Results show that the relationship varies according to the level of market power, the component of efficiency evaluated (cost, technical or allocative) and the type of banking firm (commercial bank or savings bank), suggesting that the quiet life might be a reality only for some financial institutions.